Obstetric hysterectomy in a tertiary centre: a 3-year retrospective study - More, Mayuri V.; Purandare, Nandan S.; Kaundinya, Aditi P.; Poojari, Deeksha S.; Gandi, Sudharani; Patil, Aloukika P.; Gopal, Sriram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Obstetric hysterectomy (OH) is a life-saving procedure and involves removal of uterus in cases of intractable hemorrhage. This study includes 21 cases of OH in a period of 3 years at a tertiary centre. We sought to understand the prevalence, indications and outcomes of emergency obstetric hysterectomy. Methods: This is a retrospective, observational study, conducted with the means of hospital delivery records in a tertiary care centre in Navi Mumbai. We included all patients who underwent obstetric hysterectomy in a span of 3 years between 1st April 2020 to 31st March 2023, in Dr. D.Y. Patil Hospital, Navi Mumbai, India. Results: Twenty- one OH were done in the period of study. The incidence of obstetric hysterectomy was 0.45% (452 OH per 100,000 deliveries). It was more prevalent in patients with caesarean section compared to vaginal delivery. Women between the age 25-35 years group comprised of 57.15% cases. Out of the 21 women in the study 7 women were primigravida (33.33%). Most common cause for OH was observed to be uterine atony (42.85%) followed by adherent placenta (28.57%). Maternal morbidity like admission to intensive care unit and need for blood and blood product transfusion was noted in most patients, mortality was observed in only 1 case. Neonatal mortality was nil in this study but, admission to neonatal intensive care unit was required in 7 patients. Conclusions: Although, obstetric hysterectomy kills the future reproductive prospect for a woman, it is life saving for her. Timely decision for OH can not only prevent mortality but, also morbidity for the woman. Previous caesarean section and multigravida have higher incidence of OH. Atonicity is the predominant cause for obstetric hysterectomy in this study.